Arte-educação, logística e mundo do trabalho: uma análise da integração curricular no Instituto Federal do Amapá - CARVALHO, Edvaldo do Nascimento (2025)
Art is an intrinsic human manifestation that imbues anthropic activities with poetry, aesthetic appreciation, and emotional expression, even when linked to pragmatic, political, ritual, or sociocultural tools. Thus, education cannot neglect the teaching of Art, as it constitutes an essential characteristic of the human spirit and ensures everyone’s right to access, understand, and engage with art. This dissertation examines the integration between the Art curriculum component and the technical-professional knowledge specific to Integrated High School courses at Federal Institutes. Specifically, it analyzes the Pedagogical Course Project (PPC) of the Logistics course at the Federal Institute of Education, Science, and Technology of Amapá, offered by the Santana campus.This qualitative study employs document analysis supported by bibliographic review. It originates from academic concerns about issues in Professional and Technological Education studied within the ProfEPT program, combined with the author’s professional experience as an art educator. The research synthesizes theoretical reflections on the challenges of integrating Art education with professional knowledge in Integrated High School courses. To mitigate the duality between these components, the study proposes a decolonial and liberating perspective for the Art curriculum, centered on the concept of Work as an Educational Principle, grounded in human formation, polytechnics, and omnilateral development. These considerations converge into an Educational Product proposal that seeks to unveil the world of labor through the arts.